The antiviral activity of iota-, kappa-, and lambda-carrageenan against COVID-19: A critical review - Andri Frediansyah (Elsevier, 2021)
Objective: There is no specific antiviral treatment available for coronavirus disease 2019 (COVID-19). Among the possible natural constituents is carrageenan, a polymer derived from marine algae that possesses a variety of antiviral properties. The purpose of this review was to summarize the evidence supporting carrageenan subtypes' antiviral activity against the emerging severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of COVID-19. Methods: PubMed/MEDLINE and Google Scholar searches were conducted for publications using the terms 'carrageenan', 'iota carrageenan', 'kappa carrageenan', lambda-carrageenan', 'coronavirus', 'common cold', 'rhinovirus', and 'SARS-CoV-2' search was also done in grey literature to increase our understanding. A search for the word "carrageenan" was also carried out. Most of the publications were discussed in narrative. Results: Carrageenan has been shown to have potent antiviral activity against both coronaviruses (coronavirus NL63, SARS-CoV-2) and non-coronaviruses such as dengue virus, herpes simplex virus, cytomegalovirus, vaccinia virus, vesicular stomatitis virus, sindbis virus, human immunodeficiency virus, influenza virus, human papillomavirus, rabies virus, junin virus, tacaribe virus, African swine fever, bovine herpes virus, suid herpes virus, and rhinovirus. No in vivo study has been conducted using carrageenan as an anti-SARS-CoV-2 agent. The majority of the in vivo research was done on influenza, a respiratory virus that causes common cold together with coronavirus. Thus, various clinical trials were conducted to determine the transferability of these in vitro data to clinical effectiveness against SARS-CoV-2. When combined with oral ivermectin, nasally administered iota-carrageenan improved outcome in COVID-19 patients. It is still being tested in clinics for single-dose administration. Conclusion: Though the carrageenan exhibited potent antiviral activity against SARS-CoV-2 and was used to treat COVID-19 under emergency protocol in conjunction with oral medications such as ivermectin, there is no solid evidence from clinical trials to support its efficacy. Thus, clinical trials are required to assess its efficacy for COVID-19 treatment prior to broad application.